History of atopic dermatitis – a short review from ancient to modern medicine - Jaworek, Andrzej K.; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2017)
Atopic dermatitis is one of the most common inflammatory skin diseases. The clinical hallmark of the disease, providing the most important clue for diagnosis, is intense itching of the skin. The history of dermatology is one of the most interesting elements in the history of medicine. Atopic dermatitis is a disease whose “medical entity” has been established relatively recently. A particularly fascinating aspect is the way in which the disease has been recognized as one of the greatest plagues of modern medicine. The article presents selected issues in the evolution of knowledge on the pathogenesis and treatment of atopic dermatitis. The profiles of the most famous dermatologists who have made a particularly valuable contribution to understanding the phenomenon of atopic dermatitis are outline: Jean-Louis Alibert, Ernest Henri Besnier, Ferdynand von Hebra, Marion Baldur Sulzberger. An analysis of subsequent milestones in the history of atopic dermatitis points, optimistically, to the increasingly targeted and effective treatment of the disease.